Evaluating Prospective Energy Services Demand for Residential Solar Photovoltaic (RSPV) Generated Electricity in Lagos State, Nigeria - Olalekan Jesuleye; Andrew Oriola; Adeyemi Adepoju (Journal of Digital Food, Energy & Water Systems)
Rapid urbanisation is pulling demand for energy services and emission of greenhouse gases (GHG) resulting in energy deficit, climate change and global warming. The ongoing energy crisis and degenerating climate condition demands urgent transformation of the energy system to renewable based from nonrenewable (fossil) based. To meet the growing demand for energy services and simultaneously mitigate the environmental impact of the energy sector, an accurate estimation of the demand for renewable generated electricity is vital to guide the policy makers in planning adequately for the adoption of renewable fuelled electricity generation technology in urban areas. This study evaluated the electricity demand for residential solar photovoltaic (RSPV) technology by potential household adopters of the technology in the metropolitan area of Lagos state, Nigeria. The study adopted quantitative research design with structured questionnaire to solicit information from the respondents. Three hundred and twenty-six (326) responses from the potential adopters were analysed with model for analysis of demand for energy (MADE II) and Pareto tool. The results show that the energy intensity for refrigeration services is 1.06 kWh/hh/day, entertainment services is 0.84 kWh/hh/day, computing services is 0.97 kWh/hh/day, space cooling services is 7.59 kWh/hh/day, ventilation services is 9.05 kWh/hh/day, lighting services is kWh/hh/day, cooking services 2.77 kWh/hh/day, process heating services is 6.43 kWh/hh/day and water pumping is 1.89 kWh/hh/day. The study concluded that the household energy services demand for electricity is 24.43 kWh/hh/day by the potential RSPV technology adopters and the total demand from the solar module panel of 31.59 kWh/hh/day with prospect for improvement on the energy intensity at the same output of energy services. Furtherance to this, the study recommends government intervention with formulation and implementation of dedicated policies on household appliances efficiency standard and also introduce financial schemes to support the replacement of inefficient household appliances with highly efficient ones. Further studies could include other non-common energy services that were not considered in this study. The study could also be conducted in other regions of Nigeria and also investigate the economic feasibility and behavioural acceptability of RSPV technology for effective planning of the national energy system transformation.